1995
DOI: 10.1161/01.res.76.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning of Isolated Rat Heart Is Mediated by Protein Kinase C

Abstract: Catecholamines have been implicated in the phenomenon of ischemic preconditioning. We have previously demonstrated that ischemic preconditioning against postischemic mechanical dysfunction in the isolated rat heart is mediated by the alpha 1-adrenergic receptor. The purpose of this study was to delineate the signal transduction of preconditioning distal to the alpha 1-adrenergic receptor. Our results suggest that (1) transient ischemia and alpha 1-adrenergic receptor-induced preconditioning is inhibited by pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
161
1
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 367 publications
(171 citation statements)
references
References 48 publications
7
161
1
2
Order By: Relevance
“…1A) in both groups of hearts (20 Ϯ 4 versus 19 Ϯ 3 mm Hg; n ϭ 6, p ϭ not significant). Independent laboratories have shown that pretreatment with brief ischemia, here termed TIP, prevents cardiac injury during prolonged ischemia reperfusion in association with PKC activation (9,10). In this study, we found that TIP improved LVDP recovery during reperfusion (Fig.…”
Section: Normal Base-line Morphology and In Vivo Cardiac Function In supporting
confidence: 57%
See 3 more Smart Citations
“…1A) in both groups of hearts (20 Ϯ 4 versus 19 Ϯ 3 mm Hg; n ϭ 6, p ϭ not significant). Independent laboratories have shown that pretreatment with brief ischemia, here termed TIP, prevents cardiac injury during prolonged ischemia reperfusion in association with PKC activation (9,10). In this study, we found that TIP improved LVDP recovery during reperfusion (Fig.…”
Section: Normal Base-line Morphology and In Vivo Cardiac Function In supporting
confidence: 57%
“…Stimulation of ␣ 1 -adrenergic receptors activates numerous signaling pathways within ventricular myocytes including mitochondrial K ATP channels (28), glucose transporters (42), and PKC isozymes (9). However, it is unclear which of the pathways protect acutely against injury and which of them contribute chronically to myocardial pathology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, activation of PKC can protect the heart from ischaemic injury, while PKC inhibitors block the cardioprotective effect of ischaemic preconditioning in experimental animals and in human myocytes [55][56][57][58][59][60]. On the other hand, fenoterol has known inotrophic and chronotrophic effdcts as well as other electrophysiologica l influences [40][41][42]; these are enhanced under hypoxic conditions [61].…”
Section: Discussionmentioning
confidence: 99%